2020
DOI: 10.1111/jfpp.14402
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of soy sauces made from fresh okara using two fermentation methods

Abstract: Meju, a brick made of fermented soybeans, is the main ingredient of soy sauce. It was prepared without (S) or with (OS) 40% okara fermented using Bacillus subtilis (traditional fermentation, TF) or a mixture of Aspergillus oryzae and Aspergillus niger (modified fermentation, MF). MF soy sauces (8.39% and 7.22%) showed a lower salinity than the TF soy sauce (15.41% and 16.19%), whereas the total nitrogen (TN) in MF soy sauce was twice higher than in the TF soy sauce. Amino‐type nitrogen in TF‐S (55.0%) was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This product was developed using two types of fermentations, modified using a mixture of A. oryzae and A. niger or traditional fermentation using B. subtilis. The modified fermentation exhibited excellent quality soy sauce compared with the traditional sauce regarding protease activity, amino acid content, and sensory analysis, reducing salt concentrations from 16% to 7% and shortening fermentation time from 90 to 30 days (Lee et al, 2020). The use of alternative feedstock going beyond the boundaries of conventional raw materials will provide the industry with new expertise to develop a soy sauce to fulfill specific consumer needs, as well as helping to expand and enhance soy sauce taste and variety.…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…This product was developed using two types of fermentations, modified using a mixture of A. oryzae and A. niger or traditional fermentation using B. subtilis. The modified fermentation exhibited excellent quality soy sauce compared with the traditional sauce regarding protease activity, amino acid content, and sensory analysis, reducing salt concentrations from 16% to 7% and shortening fermentation time from 90 to 30 days (Lee et al, 2020). The use of alternative feedstock going beyond the boundaries of conventional raw materials will provide the industry with new expertise to develop a soy sauce to fulfill specific consumer needs, as well as helping to expand and enhance soy sauce taste and variety.…”
Section: Highlightsmentioning
confidence: 99%
“…Soy sauce-like seasonings have also been introduced recently to fulfill consumer demands. These alternative soy sauces substitute soy sauce and wheat with different kinds of beans or grains, such as peas or broad beans, rice, quinoa or foxtail millet, as raw materials (Yamana et al, 2020), and by-products such as walnut meal (Xu et al, 2020) and okara (Lee et al, 2020). Detailed metabolomic analysis of these soy sauce-like seasonings made from different feedstock characteristic compounds and umami revealed that grain-based samples have a higher saccharide content and umami taste, whereas bean-based samples have a higher amino acid content (Yamana et al, 2020).…”
Section: Highlightsmentioning
confidence: 99%
“…Recent studies revealed that the fermentation of soybean residues with Aspergillus oryzae and Aspergillus niger offered significant improvements to the quality of soybean residues soy sauce. This fermentation process not only reduced the salt content of soy sauce but also accelerated the fermentation time, resulting in a more efficient production method (Lee et al ., 2020b). The utilisation of soybean residues and powdered yellow mealworm larvae in soy sauce production resulted in a flavourful, low‐salt product that was anticipated to mitigate the risk of vascular disease and exhibited a high antioxidant capacity (Lee & Kim, 2022).…”
Section: Application For Foodmentioning
confidence: 99%
“…The method for determining the amino acid content was modified based on Lee et al 25 The OPHs of different processings were hydrolyzed with 6 N HCl for 22 h at 110 °C and con-centrated under vacuum. The concentrated solutions were quantitative with 0.2 N HCl at 1 mL.…”
Section: Amino Acid Content Analysismentioning
confidence: 99%